MANAJEMEN STRATEGIS DALAM MENGEMBANGKAN KARAKTER RELIGIUS DI MTS RAUDLATUT THALABAH KOLAK WONOREJO NGADILUWIH KEDIRI - Nadzirotul Masruroh; Yosi Maharani; Ikhda Rokhmatin Mudawama; Aqiel Khofifi Nugroho; Muhammad Wildan Habibi; Arina Haque (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe strategic management in developing religious character at MTs Raudlatut Thalabah Kolak Wonorejo Ngadiluwih Kediri, covering three aspects: strategic planning, implementation, and evaluation. The research employed a qualitative approach with a case study design, while data were collected through observation, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing, and their validity was tested using source and technique triangulation. The results show that strategic planning is set out in the Madrasah Work Plan (RKM) through the formulation of vision and mission, identification of external opportunities and threats, identification of internal strengths and weaknesses, the setting of long-term objectives, and strategy formulation with the madrasah diniyah (madin) program as the main icon. Strategic implementation is carried out through setting annual objectives, policy making, resource allocation, organizational restructuring, incentive provision, and the development of a religious-value-based organizational culture. Strategic evaluation is conducted through reviewing the strategic foundation, comparing expected results with actual results, and taking corrective action. Religious-value-based strategic management proved effective in shaping students' religious character.